A Review of The Potential Marsilea crenata Presl. Leaves to Prevent Osteoporosis in Menopausal Women - Novita Dwi Astutik; Meike Tiya Kusuma; Jamila; Sandiena Mahesa Adzra (Journal of Research in Midwifery and Healthcare, 2025)
Women going through menopause often experience osteoporosis. One preventive measure comes from herbal plants, especially those containing isoflavones like Marsilea crenata Presl. leaves. This plant was chosen because it has been proven as antioxidant, antiinflammatory, and estrogenic effects that similar to natural hormones. The aim of this study is to investigate the potential of Marsilea crenata Presl. leaves as herbal therapy for preventing osteoporosis. The study employs a literature review approach collected from various scientific databases such as Science Direct, PubMed, and Google Scholar. Articles were selected by exclusion and inclusion criteria. The results indicate that isoflavones from Marsilea crenata Presl. leaves interact with estrogen receptors, helping to maintain balance between osteoblast and osteoclast activity and reducing bone resorption. Based on in vitro and in vivo studies, the isoflavones in Marsilea crenata Presl. leaves include daidzein, genistein, biochanin A, and formononetin. In addition, the antioxidant and anti-inflammatory properties of Marsilea crenata Presl. leaves extract can enhance its therapeutic potential. A comprehensive study explains the oral consumption of Marsilea crenata Presl. leaves extract in postmenopausal women can increase bone density and alleviate vasomotor symptoms